PHENOMENOLOGY OF PERSONAL STYLE: THE ROLE OF HAIR, MAKEUP AND STYLE DECISIONS IN IDENTITY FORMATION - Zabora, Volodymyr (Theory and practice of design, 2023)
This article is dedicated to broadening the scholarly understanding of personal style, with an emphasis on the roles of hair, makeup, and individual style decisions. We define style as a comprehensive method of self-presentation that extends beyond mere clothing choices, encompassing transformative practices that involve the entire body. Goal. The paper presents the results of a phenomenological study aimed at elucidating personal style as an embodied process of identity construction. Special attention is given to the bodily aspects manifested through makeup and hairstyle, as these elements epitomize the intersection of bodily and cultural dimensions and serve as tangible examples of material culture and body-related attitudes. Methodology. The research methodology aligns with the principles of somaesthetics, treating stylistic decisions as a form of body transformation enacted by the individual. Through the lens of conceptual phenomenology and embodiment theory, the study probes into the nuances of personal perception of the reflective functions of personal style elements and their integration into cultural contexts. The article presents results from a qualitative investigation of the individual experiences of 45 participants, drawn from semi-structured interviews. Results. The literature review encompasses an exhaustive study of pertinent scientific works, underscoring the quintessential nature of personal style as a potent form of material culture. Its intersection with embodied experience creates a complex sociocultural network of collective style. The empirical research, guided by a phenomenological conceptual framework, reveals the life experiences, motivations, and personal meanings that underpin style construction and their influence on the manifestation of the individual’s identity. Scientific Novelty. By detailing the role of body interaction in the process of personal style creation, the study contributes to a deeper understanding of identity formation and its anchoring within a globalizing cultural context. The results underscore the necessity of incorporating makeup and hairstyle into the broader concept of personal image, as these elements act as determinants of an individual’s bodily experience. Ultimately, the provided generalizations lay the groundwork for a reevaluation of personal style as a dynamic, transformative force, acting as a catalyst for the internal reconfiguration of the individual’s personality. Practical Significance. By integrating an understanding of the mind-body connection into design practice, the study emphasizes the importance of developing sensory engagement and culturally sensitive approaches. It advocates for enhanced accessibility in design, taking into consideration the bodily conditioning of individuals’ stylistic decisions. The diversity of consumers’ somatosensory experiences should guide style decisions. In this regard, a somaesthetic approach to understanding personal style offers the required granularity for designing products, environments, or interfaces that focus on the individual in relation to their life experiences.